Relevansi Penddikan Agama Islam dan Sistem Pendidikan Nasional - M. Yusuf, M. Yusuf; Marfiyanti, Marfiyanti; handriadi, handriadi (Mau`izhah : Jurnal Kajian Keislaman, 2023)
Islam is a religion that is tsumul/perfect, several aspects are stated in it, including the educational aspect, while the foundation of the Indonesian state, Pancasila and the 1945 Constitution, in several articles also states the issue of education, for example in the first principle of Pancasila. This illustrates that there is relevance between the two, especially in Islamic religious education. The aim of this research is to determine the relevance between Islamic Religious Education and National Education Goals. This research examines how the Islamic education system positions and positions the Islamic Education system as a sub-system in the national education system, taking into account various aspects that surround it, as well as the reality of Islamic education/Islamic educational institutions (madrasah/Islamic boarding school) in Indonesia. So it will be seen, the relevance between Islamic Religious Education and the goals of National Education.